The Rhetoric of Fear in Euripides' Phoenician Women*. (8th February 2017) - Papadodima, Efi
Abstract: In accordance with its notoriously rich plot, Phoenician Women explores diverse aspects of fear that affect, and are thematised by, various parties at different stages of the plot. 1 Against the background of a virtually 'irrational' and inescapable divine necessity (treated as a source of dread in itself), Euripides presents the play's central crisis as being largely determined by rational and controlled decision-making, within an array of moral disputes that enter the scene. The agents' decision-making standardly comprises diverging, conflicting, or inconsistent attitudes towards fear and related emotions, such as shame (in both past and present). The rhetoric of fear thus reflects and further highlights the characters' conflicting viewpoints, as well as Euripides' trademark tendency to toy with his audience's expectations and assumptions about ethical values and what is 'right'. This article argues that his approach is substantially different from the Aeschylean treatment of the same myth ( Seven against Thebes ). By offering a concrete and abstract treatment of the situational anxieties over war and familial feud, Euripides' rhetoric of fear ultimately shifts the focus to the complexities and contradictions of human motivation.